Analilis Pemborosan Produksi Beras Premium Dengan Metode Value Stream Mapping (VSM) - Nurhayati Rauf; Ahmad Padhil; Muhammad Subhan Mulyana Yusran; Asih Setyo Rini (Jurnal Rekayasa Proses dan Industri Terapan, 2024)
Coppo Benteng is a company that produces premium quality rice. However, there are problems in the factory activities, namely the rice production process which has several work stations. So it is necessary to analyze in identifying the causes of waste that are described with the help of value stream mapping tools to help the cause of waste in order to create a quality and guaranteed infrastructure. The research method used is the process of analyzing waste in the premium rice production process at CV. Coppo Benteng is carried out by identifying and analyzing activities that do not provide added value and providing suggestions for improvements to eliminate waste. From the results of the analysis carried out on each activity in the premium rice production process at CV. Coppo Benteng Kab. Soppeng resulted in 5 types of waste found, including waste waiting time 20%, waste unnecessary motion 10%, waste defect 5%, waste transportation 5%, and waste processing 10%. The proposed strategy that can be given is to eliminate activities that cause a lot of waste, namely in the waiting time section which must apply the latest technology and improve the infrastructure system.